Empirical Examination of Factors that Influence Official Decisions in Criminal Cases Against Police Officers - Boateng, Francis D. (American journal of criminal justice, 2024)
In the current paper, we examine departmental and court decision-making in criminal cases against police officers. The study has two objectives: 1) to examine variables that impact departmental decisions in criminal cases against police officers, and 2) to examine factors that affect case disposition/conviction decisions by the courts. To achieve these objectives, we analyzed nationally representative arrest data using multiple statistical approaches. The results obtained revealed important patterns that are critical to our understanding of how the courts and police departments decide matters relating to police criminality. For instance, victim characteristics significantly influenced decision-making by both the police agency and the court. Also, officer characteristics and crime types were important indicators of how offending officers were punished by both the courts and the agencies that employed them. Specifically, officers whose cases involved child victims and officers who were not familiar with their victims had greater odds of being convicted. The implications of our findings for policy and research in policing, especially research on police misconduct, are discussed.